Psychometric properties of Bull's Mental Skills Questionnaire in a Turkish population - Bülent O. Miçooğullari; David J. Edwards; Rıdvan Ekmekçi (University of Novi Sad, Faculty of Sport and Physical Education, 2021)
The purpose of this research was to examine the reliability and validity of Bull's Mental Skills Questionnaire (BMSQ), measuring seven psychological skills resulting in a total scale score, within Turkey. The sample consisting of 163 males and 131 females, totaling 294 athletes, completed the 28 item BMSQ. Exploratory factor analysis (EFA) and confirmatory factor analysis (CFA) were undertaken. EFA results yielded a satisfactory seven-factor solution, the same as the English version. Cronbach alpha (α) reliability indices were as follows: concentration ability (0.71), anxiety and worry management (0.63), relaxation ability (0.69), imagery ability (0.73), self-confidence (0.72), motivation (0.64) and mental preparation (0.52). The BMSQ explained 62% of the total variance. Moreover, model fit indices calculated during CFA for the 28 item and 7 sub-dimensions model of BMSQ indicated an acceptable fit [Chi-Square (ꭓ²)=541.2, df=328, ꭓ²/df=1.65, Root Mean Square Error Approximation (RMSEA)=0.05, Comparative Fit Index (CFI)=0.95, Goodness of Fit Index (GFI)=0.90, Normed Fit Index (NFI)=0.89, and Non Normed Fit Index (NNFI)=0.90]. Thus, the original 7-factor solution was supported with the data collected from Turkish participants. Results demonstrated that the BMSQ is a valid and reliable instrument for the Turkish population.